Study on the Potential for Biodiesel Production of Microalgal Consortia from Brackish Water Environment in Rayong Province, Thailand - Sunisa Ungwiwatkul; Aiya Chantarasiri (International Journal of Renewable Energy Development, 2022)
Microalgae are photoautotrophic microorganisms that can be grown in a wide variety of water environments. They are the most promising biodiesel source, with the potential to replace fossil diesel. In this study, microalgae samples were collected from the brackish water environment of three locations in Rayong province, Thailand including Phra Chedi Klang Nam (PKC), Noen Kho Canal (NKC), and Raksamae Bridge (RSM), and induced to form multi-algae communities or microalgal consortia (MC). All consortia were cultured and analyzed for their ability to produce biomass and lipid. The result was found that the biomass concentration of MC-RSM was 0.65 ± 0.05 mg.L-1, which is higher than 1.2 and 1.5-times of MC-PCK and MC-NKC, respectively. The most common microalgae species found under all cultures were green algae (Chlorophyta) and diatom (Bacillariophyta), and the dominant species was the green algae, Chlorella sp. The lipid content of all samples ranged from 28.07 ± 0.60 to 33.21 ± 0.79% of dry weight, and the highest value was noticed in the MC-RSM sample. The fatty acid composition of fatty acid methyl ester (FAME) was also evaluated as feasibility for biodiesel production. FAME profiles of each sample showed high amounts of saturated fatty acids (SFAs) ranging from 67.82%-71.31% of total fatty acids. The majority of the SFAs in all were palmitic acid (C16:0) followed by myristic acid (C14:0, and stearic acid (C18:0). Therefore, all microalgal consortia showed great fatty acid profiles and these have the potential for use as feedstock for biodiesel production.